New development of organizational commitment: A critical review (1960-2009) - WeiBo, Z.; Kaur, S.; Jun, W. (Academic Journals, 2010)
This paper reviews the characteristics of main approaches to Organizational Commitment from the beginning of conception of Commitment in Becker (1960) till today, provides an overview of different eras and domains. Then discuss some new development of Organizational Commitment in commitment tendency or combined influence to organizational outcomes. This paper will argue some of thinking and ideas developed so far do provide the basic building blocks for suggesting a conceptualization that will attempt to clarify and to better represent the concept of organizational commitment. The advantages of suggested theory and its implications for the understanding of organizational commitment and future research on it are discussed.